The Contribution of Ibnu Khaldun’s Economic Thoughts - Ahmad Ajib Ridlwan; Imam Mawardi (Universitas Darussalam Gontor, 2019)
This article examines Ibnu Khaldun’s economic thought in his literature ‎entitled Muqaddimah. Discussing this idea is crucial due to his great contribution to ‎the future development of Islamic economy. In addition, Ibnu Khaldun’s thought has ‎contributed further to an economic science until becoming a prominent theory in 18th ‎and 19th century far before many experts such as Adam Smith, David Ricardo, Leon ‎Walras, Karl Marx, and the others established their theories. Ibnu Khaldun’s thought ‎is considered fundamental, not only due to the fact that he precedes any Western ‎economists but he is also an expert of extensive sciences besides Economics so he ‎possess an outstanding ability to to write his Economics in a complete perspective. ‎Among his contributions to both macro and micro Economics, Ibnu Khaldun ‎occassionally proposed his Economics in 14th century when Europe was still in pre-‎modern era. This study concludes that, historically, Ibnu Khaldun’s Economics have ‎existed far before modern Western scholars defined their ideas. It is not exaggerating ‎therefore to call Ibnu Khaldun as Father of Economics in the case of his ideas of ‎taxes, international trades, political and civilization developments are all crucial to ‎be taken into account in current context for prosperity in society and state.‎